The importance of methods for developing physical fitness qualities (endurance) and their impact on junior football players - Madani, Mohamed; aatab, brahim (sports creativity, 2025)
The modern concept of physical education and sports, and its contemporary meaning, transcends the mere notion of games or exercises, which some once considered an obligatory duty for students, performed once a week. This concept has undergone a significant transformation, evolving into a scientific and practical discipline, much like other sciences, with the aim of elevating the individual and society both qualitatively and quantitatively. Physical education and sports contribute to improved performance, maintain the health and physical development of the athlete or individual, and cultivate physical fitness qualities (endurance, strength, flexibility, speed, etc.). They also contribute to acquiring knowledge and understanding of the fundamentals of movement and developing a habit of engaging in sports activities. Among the most widely practiced and popular activities is football, which has recently witnessed significant advancements in training and development methods for both players and coaches. The factors influencing them physically, technically, psychologically, and tactically are reflected in their performance and level in competitions. Hence the necessity of focusing on the physical aspect of sports, which aims to provide the necessary capacity to develop and enhance various aspects of physical fitness. These aspects represent the foundation of athletic performance, giving them a prominent place among specialists and making them of paramount importance to football coaches due to their role in improving player performance and elevating them to a high level. Football requires good physical fitness to enable players to keep pace with the fast rhythm of matches, which necessitates high-level training to develop various aspects of physical fitness. Among the most important aspects of physical fitness is consistency, which is considered one of the biggest shortcomings in our national football championships, whether in the first division or the lower divisions. For example, some teams from the Medea province (Ksar El Boukhari, Bougzoul, Segouane, Berrouaghia), in the under-15 category (15-17 years old), can be considered.